Whole strains vs MGEs in short and longterm transmission of ESBL genes between healthcare and community settings in Uganda - Yaovi Mahuton Gildas Hounmanou; Agnes Wanyana; Stephen Alafi; Fred Wabwire-Mangen; Henrik Christensen; John Elmerdahl Olsen; Denis Karuhize Byarugaba (Scientific Reports, 2023)
Abstract Multidrug-resistant ESBL-producing Escherichia coli are a leading cause of infections in hospital and community settings. Based on samples from two hospitals in Uganda and households of inpatients we tested the hypothesis that ESBL E. coli and/or their resistance determinants could spread within the healthcare and community settings through discharged patients that were still colonized. We used bacterial culture, susceptibility testing whole genome sequencing and detailed bioinformatics analysis to test the above hypothesis. Genome analysis revealed presence of predominantly bla CTX-M-15 and bla OXA-1 genes with a total resistome with genes belonging to 14 different classes of antimicrobials. Short-term cases of strain sharing were reported within each setting and strains from the two settings were found to cluster together based on their overall resistome. Long-term horizontal transfer of ESBL genes by various IncF and IncY types of plasmids shared between healthcare and community settings was demonstrated. Based on hybrid assembly, plasmid reconstruction and phylogenetic analyses, our study suggests that while the dissemination of AMR between healthcare and community settings in the short-term is possible at whole strain level, the long-term transmission between healthcare and communities is sustained by the transfer of plasmids circulating across niches and disseminating related resistomes.